ESTIMATION OF BODY WEIGHT AND MORPHOMETRIC TRAITS IN PANCAKE TORTOISE (Malacochersus tornieri) USING FACTOR SCORES ANALYSIS - Kperegbeyi, J. I.; Akaine, F.; Onwumere-Idolor, O.S.; Okhale, O.E. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study used factor score regression to predict body weight from morphometric traits in the pancake tortoise (Malacochersus tornieri). A total of 96 sexually matured pancake tortoises were sampled, with morphometric measurements including straight carapace length (SCL), carapace width (CW), straight plastron length (SPL), plastron width (PW), and carapace circumference (CC), being analyzed. All traits followed a normal distribution, as confirmed by descriptive analysis (P > 0.05). Correlation analysis demonstrated a strong positive association (r = 0.916, P = 0.000) between body weight (BWT) and each linear measurement, indicating that larger morphometric dimensions are associated with heavier animals. Regression results showed moderate influence for both SPL and CC (β = 0.513 and 0.308, respectively); however, they did not reach statistical significance (P > 0.05). This finding is likely influenced by high collinearity, limited data points, or an insufficient capacity to capture soft tissue variations. A factor analysis revealed two primary factors that account for 73.75% of the total variance. The first factor is characterized by strong loadings from SCL (0.907) and CW (0.905), while the second factor is defined by SPL (0.860), PW (0.799), and CC (0.697). These findings demonstrate that factor score analysis effectively mitigates multicollinearity, providing a robust framework for modeling Malacochersus tornieri, body weight that aligns with prior morphometric research.